2022
DOI: 10.1177/09544089221100784
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of variable-temperature drying ofCamellia oleiferaseeds

Abstract: The processing method of Camellia oleifera fruit used in the industry was investigated, that is, fresh C. oleifera fruit was shelled in the drying equipment first and then the remaining C. oleifera seeds returned until the target moisture content (about 10% d.b.) was reached. The variable-temperature drying of C. oleifera seeds was investigated for the first time and the drying process was optimized and compared with constant-temperature drying. Two independent variables, including hot air drying temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…However, Dehghan-Manshadi et al (2020) found that the peroxide values of flaxseed oil samples subjected to IRSBD were higher compared to those of SBD at the same temperature, and the content of linoleic acid also changed. Therefore, the appropriate drying temperature is critical to the quality of the sample, and variable temperature drying can sometimes be more effective than constant temperature drying (Li, Pan, et al, 2023;Men et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, Dehghan-Manshadi et al (2020) found that the peroxide values of flaxseed oil samples subjected to IRSBD were higher compared to those of SBD at the same temperature, and the content of linoleic acid also changed. Therefore, the appropriate drying temperature is critical to the quality of the sample, and variable temperature drying can sometimes be more effective than constant temperature drying (Li, Pan, et al, 2023;Men et al, 2022).…”
Section: Introductionmentioning
confidence: 99%